Dehydrated material and preparation method thereof, positive electrode material and preparation method thereof, and lithium ion battery
By using nickel-cobalt hydroxide precursor materials and dehydration materials prepared by lithium sources, and using low-temperature heating and dehydration technology, the problem of high moisture content in the manufacturing of high-nickel multivariate cathode materials is solved, the sintering capacity and electrochemical performance are improved, and a more efficient production process is achieved.
Patent Information
- Application Number
- CN202411767224.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
In the manufacturing process of high nickel multivariate cathode materials, the high moisture content in the raw materials leads to difficulties in dehydration control, affecting yield and electrochemical performance, and at the same time increasing the burden and production cost of the kiln.
A dehydration material is provided, which is mainly composed of nickel-cobalt hydroxide precursor material and a lithium source. By low-temperature heating and dehydration treatment, the moisture content in the lithium source is reduced and the loose density is increased, thereby improving the loading capacity and electrochemical performance of the subsequent sintering process.
It significantly improves the electrochemical performance and sintering capacity of the cathode material, reduces the amount of water vapor generated, avoids adverse effects of the kiln, and improves production efficiency and product quality.
Smart Images

Figure CN119569138A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials for lithium ion batteries, and in particular to a dehydrated material and a preparation method thereof, a positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] In actual production, the manufacture of high-nickel multi-element cathode materials faces the following problems: Because the raw materials contain a large amount of water, it is inevitable that a large amount of water will be introduced during the production process. Therefore, dehydration control is particularly critical. How to regulate the dehydration reaction process to increase the output of ternary cathode materials is the focus of applied research.
[0003] At present, in order to increase the production capacity of positive electrode materials, the precursor and lithium hydroxide monohydrate are usually dehydrated during the pre-sintering process. The theoretical water content of lithium hydroxide monohydrate is as high as 42.93%, which is usually removed during the high-temperature pre-sintering process in the kiln. However, the loading capacity of this method is low, and more sintering equipment needs to be introduced during the pre-sintering process to meet the input of subsequent process materials. In addition, the mass of the material before and after pre-sintering changes greatly, which cannot match the formal sintering capacity. In actual production, the same heating equipment is used for pre-sintering and formal sintering. The traditional process directly mixes the lithium source and the precursor and pre-sinters them in a bowl. The bowl load is 90%, and the mass loss after pre-sintering is as high as 26%. At the same time, the material in the sagger will become compact. When the number of sintering equipment remains unchanged, the sagger load will not reach 90% during the formal sintering, and there will be only 60% to 70%. The space of the sagger is not fully utilized, which is different from the assumption that each sagger is loaded with 90%, resulting in a mismatch in the formal sintering capacity.
[0004] In addition, the above method has the following problems: First, the excessively high moisture content in the kiln leads to a decrease in the oxygen concentration, which in turn affects the sufficiency of the oxidation reaction, causing the produced high-nickel multi-element positive electrode material to have performance defects (nickel is difficult to oxidize to a high-valent state), reducing the product's pass rate and electrochemical performance; Second, the high moisture content will have an adverse effect on the kiln, which not only increases production costs, but may also introduce new impurities.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first object of the present invention is to provide a dehydrated material, which has a low water content and a high apparent density. It can increase the loading amount during the subsequent pre-sintering or sintering process, maximize the use of sintering equipment, and significantly improve production capacity. At the same time, due to the low water content in the dehydrated material, the production of water vapor during the subsequent pre-sintering and sintering processes is significantly reduced, thereby improving the electrochemical performance of the cathode material; it also avoids adverse effects on the kiln. It solves the problems of low loading amount that requires introducing more sintering equipment during the pre-sintering process, large changes in the mass of the material before and after pre-sintering resulting in inability to match the production capacity of formal sintering, and high water content in the kiln leading to a decline in the performance of the cathode material and adverse effects on the kiln.
[0007] The second object of the present invention is to provide a preparation method of a dehydrated material. The dehydrated material prepared by this method has a low water content and a high apparent density, effectively increasing the loading amount during the subsequent pre-sintering and sintering processes and reducing the adverse effects caused by excessive water content.
[0008] The third object of the present invention is to provide a cathode material, which has excellent electrochemical performance and low production cost.
[0009] The fourth object of the present invention is to provide a preparation method of a cathode material. Using the dehydrated material to prepare the cathode material, the generation amount of water vapor during the pre-sintering and sintering processes is low, which can ensure a sufficient oxygen atmosphere to oxidize nickel to a high valence state, thereby improving the electrochemical performance of the cathode material.
[0010] The fifth object of the present invention is to provide a cathode sheet.
[0011] The sixth object of the present invention is to provide a lithium-ion battery.
[0012] In order to achieve the above objects of the present invention, the following technical solutions are specifically adopted:
[0013] The present invention first provides a dehydrated material, which mainly consists of a nickel-cobalt hydroxide precursor material and a lithium source; the apparent density of the dehydrated material is 0.75 - 1.5 g / cm 3 ; the mass fraction of water in the dehydrated material < 0.4 wt%.
[0014] Furthermore, the chemical formula of the nickel-cobalt hydroxide precursor material is Ni x Co y M 1-x-y (OH)2, where 0 < x < 1, 0 < y < 1, 0 ≤ 1 - x - y ≤ 0.2, and M includes at least one of Co, Al, Ta, Mn, Zr, Mg, Ca, Ge, Y, W, B, Ce, Sr, Nb, and Ti elements; furthermore, 0.8 ≤ x < 1.
[0015] Furthermore, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate.
[0016] Furthermore, the molar ratio of the nickel cobalt hydroxide precursor material to the lithium element in the lithium source is 1:0.7-1.2.
[0017] Furthermore, the molar ratio of the nickel cobalt hydroxide precursor material to the lithium element in the lithium source is 1:0.95-1.1.
[0018] Furthermore, the tap density of the dehydrated material is 1.38-1.7 g / cm 3 .
[0019] The present invention further provides a method for preparing the dehydrated material, comprising the following steps: mixing a nickel cobalt hydroxide precursor material and a lithium source to be dehydrated, and then dehydrating the mixture under conditions of continuous introduction of gas or negative pressure to obtain the dehydrated material.
[0020] Furthermore, the preparation method of the dehydrated material specifically includes: mixing the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated, loading them into a sagger, placing them in a sintering device, continuously introducing gas, and performing the dehydration at 100-300°C.
[0021] Furthermore, the loading capacity of the sagger is 70% to 100% of the volume of the sagger, and further 85% to 95%.
[0022] Furthermore, the gas includes air and / or nitrogen.
[0023] Furthermore, the gas flow rate is 0.1 to 5 L / min, and further 0.5 to 3 L / min.
[0024] Furthermore, the preparation method of the dehydrated material specifically includes: mixing the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated in a mixing device, and after the mixing is completed, reducing the rotation speed of the mixing device and increasing the temperature of the mixing device, and performing the dehydration at 100-300°C under negative pressure conditions.
[0025] Furthermore, the rotation speed of the mixing device is reduced to 100-1000 rpm, and further to 100-600 rpm.
[0026] Furthermore, the dehydration time is 60 to 180 minutes.
[0027] Furthermore, the dehydration air pressure is 0.02-0.07 MPa, and further 0.02-0.04 MPa.
[0028] Furthermore, the mixing rotation speed is 300 to 3500 rpm.
[0029] Furthermore, the mixing rotation speed is 1000-3000 rpm.
[0030] Furthermore, the mixing time is 1 to 20 minutes.
[0031] Furthermore, the mixing time is 3 to 10 minutes.
[0032] Furthermore, the dehydration temperature is 140-240°C.
[0033] Furthermore, the dehydration time is 30 to 480 minutes.
[0034] Furthermore, the dehydration time is 60 to 240 minutes.
[0035] Further, before the dehydration, the sum of the masses of the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated is m1, and the mass of the dehydrated material obtained after the dehydration is m2, (m1-m2) / m1=9% to 40%;
[0036] Furthermore, the bulk density of the mixed material obtained after the mixing is AD1, and the bulk density of the dehydrated material obtained after the dehydration is AD2, (AD2-AD1) / AD1=16% to 40%.
[0037] Furthermore, the lithium source to be dehydrated includes at least one of lithium hydroxide monohydrate, anhydrous lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate.
[0038] The present invention further provides a positive electrode material, which is mainly prepared from the dehydrated material.
[0039] Furthermore, the bulk density of the positive electrode material is 1.5 to 1.9 g / cm 3 .
[0040] Furthermore, the tap density of the positive electrode material is 2.3 to 2.6 g / cm 3 .
[0041] The present invention also provides a method for preparing the positive electrode material, comprising the following steps: pre-sintering and sintering the dehydrated material in sequence.
[0042] The present invention further provides a positive electrode sheet, comprising the positive electrode material.
[0043] The present invention also provides a lithium ion battery, comprising the positive electrode sheet.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] (1) The dehydrated material provided by the present invention has low water content and high bulk density, which can increase the loading capacity during the subsequent pre-sintering and sintering process, greatly increase the output, and increase the subsequent sintering capacity without changing the sintering equipment. In addition, due to the low water content in the dehydrated material, the output of water vapor during the subsequent pre-sintering and sintering process is significantly reduced, which fully ensures the oxygen atmosphere during high-temperature sintering, so that the positive electrode material has better electrochemical performance.
[0046] (2) The dehydrated material provided by the present invention has a high tap density.
[0047] (3) The use of the dehydrated material provided by the present invention will not cause performance degradation of the final positive electrode material product, and can significantly increase the loading capacity per unit volume of the sagger during subsequent pre-sintering or formal sintering, thereby improving the sintering yield and production capacity.
[0048] (4) The method for preparing dehydrated materials provided by the present invention dehydrates the lithium source before pre-sintering and formal sintering, which can significantly increase the material loading amount in the subsequent pre-sintering and formal sintering processes, greatly improve the output, and reduce the generation of water vapor in the subsequent sintering process, ensuring sufficient oxygen atmosphere to oxidize nickel to a high valence state, thereby improving the electrochemical performance of the positive electrode material.
[0049] (5) The method for preparing the dehydrated material provided by the present invention performs low-temperature heating dehydration treatment after or during mixing, and continuously introduces gas or controls negative pressure conditions, so that the moisture in the lithium source can be discharged promptly and quickly, thereby shortening the dehydration time. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0051] Figure 1 This is a SEM image of the dehydrated material obtained in Example 1 provided by the present invention;
[0052] Figure 2 This is a SEM image of the dehydrated material obtained in Example 2 provided by the present invention;
[0053] Figure 3 This is a SEM image of the dehydrated material obtained in Example 3 provided by the present invention;
[0054] Figure 4 This is a SEM image of the dehydrated material obtained in Example 4 provided by the present invention;
[0055] Figure 5 This is a cross-sectional SEM image of the dehydrated material obtained in Example 1 provided by the present invention;
[0056] Figure 6 This is a cross-sectional SEM image of the dehydrated material obtained in Example 2 provided by the present invention;
[0057] Figure 7 This is a cross-sectional SEM image of the dehydrated material obtained in Example 3 provided by the present invention;
[0058] Figure 8 This is a cross-sectional SEM image of the dehydrated material obtained in Example 4 provided by the present invention;
[0059] Fig. 9 This is a SEM image of the positive electrode material prepared in Example 1 provided by the present invention;
[0060] Fig.10 This is a SEM image of the positive electrode material prepared in Example 2 provided by the present invention;
[0061] Fig.11 This is a SEM image of the positive electrode material prepared in Example 3 provided by the present invention;
[0062] Fig.12 This is a SEM image of the positive electrode material prepared in Example 4 provided by the present invention;
[0063] Fig.13 A comparison diagram of thermogravimetric analysis curves of target temperatures of the uniformly mixed material provided by the present invention of 160° C., 180° C., 200° C., and 220° C.;
[0064] Fig.14 A comparison chart of the cycle performance of Examples 1 to 4 and Comparative Example 1 provided by the present invention;
[0065] Fig.15 The charge and discharge curves of Example 1 provided by the present invention at different current densities;
[0066] Fig.16 A comparison chart of the cycle performance of Example 5 and Comparative Example 2 provided by the present invention;
[0067] Fig.17 The charge and discharge curves of Example 5 provided by the present invention at different current densities;
[0068] Fig.18 A schematic flow chart of the method for preparing the positive electrode material provided by the present invention. DETAILED DESCRIPTION
[0069] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0070] In a first aspect, the present invention provides a dehydration material, which is mainly composed of a nickel cobalt hydroxide precursor material and a lithium source.
[0071] The bulk density of the dehydrated material is 0.75-1.5 g / cm 3 ; Including but not limited to 0.75g / cm 3 , 0.8g / cm 3 , 1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 Any point value in or any range of values between them.
[0072] The mass fraction of water in the dehydrated material is less than 0.4wt%, including but not limited to any one of 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt% or any range between two of them.
[0073] The dehydrated material provided by the present invention has low water content and high loose density, and can increase the loading capacity in the subsequent pre-sintering and sintering processes, greatly improve the output, and increase the subsequent sintering capacity without changing the sintering equipment.
[0074] In addition, the dehydrated material provided by the present invention effectively reduces the water content, has high dehydration quality, and the loose density of the dehydrated material is significantly improved. More materials can be loaded during pre-sintering, and the loading capacity can be significantly increased. When the sintering equipment remains unchanged, the pre-sintering loading capacity is increased, and the loading capacity of each sagger can reach more than 80% during formal sintering, so that the sintering equipment is used to the maximum extent, and the production capacity is significantly improved. The problem that the quality of the material before and after pre-sintering is greatly changed in the prior art, which makes it impossible to match the formal sintering capacity, is solved.
[0075] Meanwhile, due to the low water content in the dehydrated material, the production of water vapor during the subsequent pre-sintering and sintering processes is significantly reduced, fully ensuring the oxygen atmosphere during high-temperature sintering and enabling the cathode material to have better electrochemical performance.
[0076] Among them, the nickel-cobalt hydroxide precursor material can be a nickel-cobalt precursor doped with metal or non-metal, or an undoped nickel-cobalt precursor.
[0077] In some specific embodiments, the chemical formula of the nickel-cobalt hydroxide precursor material is Ni x Co y M 1-x-y (OH)2.
[0078] Among them, 0 < x < 1, 0 < y < 1, 0 ≤ 1 - x - y ≤ 0.2. x includes, but is not limited to, any point value among 0.1, 0.2, 0.3, 0.5, 0.6, 0.8, 0.85, 0.9, 0.95, 0.98 or the range value between any two of them; y includes, but is not limited to, any point value among 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or the range value between any two of them; 1 - x - y includes, but is not limited to, any point value among 0, 0.01, 0.03, 0.05, 0.08, 0.1, 0.12, 0.15, 0.17, 0.2 or the range value between any two of them.
[0079] M is a doping element, and M includes at least one of Co, Al, Ta, Mn, Zr, Mg, Ca, Ge, Y, W, B, Ce, Sr, Nb, and Ti elements. Doping is beneficial to further improving the electrochemical performance of the nickel-cobalt hydroxide precursor material.
[0080] Preferably, 0.8 ≤ x < 1; that is, the nickel-cobalt hydroxide precursor material is a high-nickel precursor.
[0081] In some specific embodiments, the lithium source includes at least one of lithium hydroxide (i.e., anhydrous lithium hydroxide), lithium carbonate, lithium acetate, and lithium nitrate.
[0082] In some specific embodiments, the molar ratio of lithium element in the nickel-cobalt hydroxide precursor material to the lithium source is 1:0.7 - 1.2, including, but not limited to, any point value among 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2 or the range value between any two of them.
[0083] In some specific embodiments, the molar ratio of lithium element in the nickel-cobalt hydroxide precursor material to the lithium source is 1:0.95 - 1.1.
[0084] The dehydrated material provided by the present invention has a high tap density. In some specific embodiments, the tap density of the dehydrated material is 1.38 to 1.7 g / cm 3 , including but not limited to 1.38g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 Any point value in or any range of values between them.
[0085] In a second aspect, the present invention provides a method for preparing the dehydrated material, comprising the following steps: uniformly mixing a nickel cobalt hydroxide precursor material and a lithium source to be dehydrated, and then dehydrating the mixture in an atmosphere of continuous gas flow or under negative pressure conditions, and obtaining the dehydrated material after the dehydration is completed.
[0086] The preparation method of the dehydrated material provided by the present invention dehydrates the lithium source in the mixing stage before pre-sintering and formal sintering, which can significantly increase the material loading amount in the subsequent pre-sintering and formal sintering processes, greatly improve the output, and reduce the generation of water vapor in the subsequent sintering process, ensuring a sufficient oxygen atmosphere to oxidize nickel to a high valence state, thereby improving the electrochemical performance of the positive electrode material.
[0087] In addition, the present invention adopts lithium source low-temperature pre-dehydration technology, which mainly removes water from the lithium source (such as lithium hydroxide monohydrate). The dehydration quality can reach 13%, and the loose density of the material after dehydration is significantly improved. More materials can be loaded during pre-sintering and loading, and the loading capacity can be increased by 35.99%. When the sintering equipment remains unchanged, the pre-sintering loading capacity is increased, and the loading capacity of each sagger can reach more than 80% during formal sintering, so the sintering equipment is used to the maximum extent, which significantly improves the production capacity.
[0088] At the same time, the preparation method of the dehydrated material provided by the present invention performs low-temperature heating dehydration treatment after or during mixing, and continuously introduces gas or controls negative pressure conditions, which can promptly and quickly discharge the water in the lithium source, thereby shortening the dehydration time. Moreover, dehydration under negative pressure conditions is more efficient, the dehydration is relatively more complete, and the material quality rate loss after dehydration is higher.
[0089] In addition, the present invention adopts a method of mixing the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated and then dehydrating at the same time, which can ensure the accuracy of the Li element and the precursor ratio compared to the method of first dehydrating the lithium source and then mixing with the precursor. Because the mixing of the lithium source and the precursor is strictly calculated through the lithium ratio, if the lithium source is dehydrated separately first, it is impossible to ensure that all the monohydrated lithium hydroxides in the lithium source are fully converted into anhydrous lithium hydroxide, and the relative molecular weights of monohydrated lithium hydroxide and anhydrous lithium hydroxide are different, which leads to errors in calculating the Li element and the precursor ratio. In addition, if the lithium source is dehydrated separately first, due to the low density of the lithium source, when the dehydration speed is fast, water vapor will take out some lithium source particles, causing material splashing and easy damage to the equipment.
[0090] Specifically, the dehydration is mainly to remove water from the lithium source. After the dehydration, the particles of the lithium source become smaller, and are evenly distributed with the nickel cobalt hydroxide precursor material, so that the mixing effect is better and the combination with the nickel cobalt hydroxide precursor material is tighter.
[0091] In some specific embodiments, the preparation method of the dehydrated material specifically includes: mixing the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated and loading them into a sagger, placing the sagger in a sintering device, continuously introducing gas into the sintering device, and performing the dehydration at 100-300°C. This method is to perform low-temperature heating dehydration after mixing. This method can be completed directly using a sintering furnace.
[0092] Preferably, the loading capacity of the sagger is 70% to 100% of the volume of the sagger, including but not limited to any point value of 70%, 75%, 80%, 85%, 90%, 95%, 100% or any range value between two of them; this loading capacity can maximize the use of the sagger volume, reduce material splashing, and improve the quality of collected materials. More preferably, the loading capacity of the sagger is 85% to 95% of the volume of the sagger.
[0093] Preferably, the gas comprises air and / or nitrogen.
[0094] Preferably, the gas flow rate is 0.1-5 L / min, including but not limited to any one of 0.1 L / min, 0.3 L / min, 0.5 L / min, 1 L / min, 1.5 L / min, 2 L / min, 2.5 L / min, 3 L / min, 3.5 L / min, 4 L / min, 4.5 L / min, 5 L / min or any range between two thereof; this can ensure that the water vapor is taken out in time. More preferably, the gas flow rate is 0.5-3 L / min.
[0095] In some specific embodiments, the preparation method of the dehydrated material specifically includes: mixing the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated in a mixing device, after the mixing is completed, reducing the rotation speed of the mixing device, and increasing the temperature of the mixing device, and performing the dehydration at 100-300°C under negative pressure conditions. During the dehydration process, the generated water will be quickly discharged due to the negative pressure, which can effectively shorten the dehydration time. The method is to perform low-temperature heating dehydration during the mixing process, that is, dehydration is performed directly in the mixing device. During the dehydration process of mixing, the precursor and the lithium source are in a flowing state in the material tank, and the mixing device is a tank wall heating, so that the lithium source in the material tank can contact the tank wall, so that the lithium source is dehydrated more completely and the dehydration speed is faster, which is specifically reflected in the higher mass loss rate and the shorter dehydration time.
[0096] Preferably, the rotation speed of the mixing device is reduced to 100-1000rpm, including but not limited to any point value of 100rpm, 200rpm, 300rpm, 500rpm, 600rpm, 800rpm, 1000rpm or any range value between two thereof; since the precursor and the lithium source are both micron-sized powders, high rotation speed will cause the material to splash in the form of dust. If dehydrated in this state, water vapor will clog the exhaust pipe with dust, which may easily cause damage to the equipment. Therefore, the rotation speed needs to be reduced before dehydration. More preferably, the rotation speed of the mixing device is reduced to 100-600rpm.
[0097] Preferably, the dehydration time is 60 to 180 minutes, including but not limited to any one of 60 minutes, 70 minutes, 80 minutes, 100 minutes, 120 minutes, 130 minutes, 150 minutes, 160 minutes, and 180 minutes, or any range between two of them. Thanks to the existence of slight negative pressure in the mixing equipment, the generated water vapor will be quickly discharged, which can further shorten the dehydration time.
[0098] Preferably, the dehydration air pressure is 0.02-0.07 MPa, including but not limited to any point value of 0.02 MPa, 0.03 MPa, 0.04 MPa, 0.05 MPa, 0.06 MPa, 0.07 MPa or a range value between any two of them; more preferably, it is 0.02-0.04 MPa.
[0099] In some specific embodiments, the mixing rotation speed is 300-3500 rpm, including but not limited to any point value of 300 rpm, 500 rpm, 600 rpm, 800 rpm, 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm or any range value between two of them.
[0100] In some specific embodiments, the mixing rotation speed is 1000-3000 rpm, including but not limited to any point value of 1000 rpm, 1200 rpm, 1500 rpm, 1800 rpm, 2000 rpm, 2300 rpm, 2500 rpm, 2800 rpm, 3000 rpm or any range value between two of them.
[0101] In some specific embodiments, the mixing time is 1 to 20 min, including but not limited to any one of 1 min, 3 min, 5 min, 8 min, 10 min, 12 min, 13 min, 15 min, 18 min, and 20 min, or a range between any two of them.
[0102] In some specific embodiments, the mixing time is 3 to 10 minutes, including but not limited to any one of 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, and 10 minutes, or a range between any two of them.
[0103] In some specific embodiments, the dehydration temperature is 140-240° C., including but not limited to any point value of 140° C., 150° C., 160° C., 180° C., 200° C., 220° C., 240° C., or any range value between two of them. This temperature is conducive to fully removing water from the lithium source while taking into account the performance of the positive electrode material.
[0104] In some specific embodiments, the dehydration time is 30 to 480 minutes, including but not limited to any one of 30 minutes, 40 minutes, 60 minutes, 80 minutes, 90 minutes, 100 minutes, 120 minutes, 150 minutes, 180 minutes, 210 minutes, 240 minutes, 360 minutes, and 480 minutes, or any range between two of them. This time is conducive to fully removing water from the lithium source while taking into account the performance of the positive electrode material.
[0105] In some specific embodiments, the dehydration time is 60 to 240 min, including but not limited to any one of 60 min, 80 min, 90 min, 100 min, 120 min, 150 min, 180 min, 210 min, and 240 min, or a range between any two of them.
[0106] In some specific embodiments, the sum of the masses of the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated before the dehydration is m1, and the mass of the dehydrated material obtained after the dehydration is m2, (m1-m2) / m1=9% to 40%. Wherein (m1-m2) / m1 includes but is not limited to any point value of 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or any range value between two of them. It can be seen that the dehydration method provided by the present invention has high dehydration efficiency.
[0107] In some specific embodiments, the bulk density of the mixed material obtained by mixing the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated is AD1, and the bulk density of the dehydrated material obtained after the dehydration is AD2, (AD2-AD1) / AD1=16% to 40%, including but not limited to any point value of 16%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 37%, 40% or any range value between the two. By using the dehydration method provided by the present invention, the bulk density of the dehydrated material is significantly improved.
[0108] In some specific embodiments, the lithium source to be dehydrated includes at least one of lithium hydroxide monohydrate, anhydrous lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate. Among them, lithium hydroxide monohydrate has a high water content, and if it is not dehydrated, it is easy to affect the qualified rate and electrochemical performance of the prepared positive electrode material.
[0109] In a third aspect, the present invention provides a positive electrode material, which is mainly made from the dehydrated material;
[0110] The positive electrode material has excellent electrochemical performance and low production cost.
[0111] In some specific embodiments, the bulk density of the positive electrode material is 1.5 to 1.9 g / cm 3 , including but not limited to 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 Any point value in or any range of values between them.
[0112] In some specific embodiments, the tap density of the positive electrode material is 2.3 to 2.6 g / cm 3 , including but not limited to 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm3 Any point value in or any range of values between them.
[0113] In a fourth aspect, the present invention provides a method for preparing the positive electrode material, comprising the steps of pre-sintering and sintering the dehydrated material in sequence, Fig.18 As shown. Pre-sintering can deeply dehydrate the lithium source and the precursor at a higher temperature at the same time, change their structure, and make the lithium-containing compound evenly distributed on the surface of the precursor for pre-reaction and sintering, in preparation for the subsequent formal sintering to form a stable layered structure. Sintering is to sinter the pre-sintered product at a higher temperature to obtain the final positive electrode material.
[0114] The method for preparing the positive electrode material provided by the present invention uses dehydrated materials as raw materials, and can improve the electrochemical performance of the positive electrode material.
[0115] In some specific embodiments, during the pre-sintering process, the loading amount is 70% to 100% of the volume of the sagger, including but not limited to any point value of 70%, 75%, 80%, 85%, 90%, 95%, 100% or a range value between any two of them; preferably 85% to 95%.
[0116] In some specific embodiments, the pre-sintering temperature is 600-700°C, including but not limited to any one of 600°C, 630°C, 650°C, 680°C, and 700°C, or a range between any two of them; the pre-sintering time is 6-12h, including but not limited to any one of 6h, 7h, 8h, 9h, 10h, and 12h, or a range between any two of them.
[0117] In some specific embodiments, the pre-sintering atmosphere includes air atmosphere and / or oxygen atmosphere.
[0118] In some specific embodiments, the sintering temperature is 700-800°C, including but not limited to any one of 700°C, 730°C, 750°C, 780°C, and 800°C, or a range between any two of them; the sintering time is 12-24h, including but not limited to any one of 12h, 15h, 18h, 20h, 22h, and 24h, or a range between any two of them.
[0119] In some specific embodiments, the sintering atmosphere includes an oxygen atmosphere.
[0120] In some specific embodiments, the sintering further comprises at least one step of crushing, washing, drying and screening.
[0121] In a fifth aspect, the present invention provides a positive electrode sheet comprising the positive electrode material.
[0122] The positive electrode sheet has good electrochemical performance and low production cost.
[0123] Optionally, the positive electrode sheet further includes a binder and / or a conductive agent, which is not limited in the present invention.
[0124] In a sixth aspect, the present invention provides a lithium-ion battery, comprising the positive electrode sheet.
[0125] The lithium-ion battery has excellent comprehensive electrochemical performance, not only high capacity and high first coulombic efficiency, but also good cycle performance.
[0126] Optionally, the lithium-ion battery further includes a negative electrode sheet, a separator and an electrolyte, which is not limited in the present invention.
[0127] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0128] Example 1
[0129] The preparation method of the dehydrated material provided in this embodiment comprises the following steps:
[0130] (1) The lithium source LiOH·H2O to be dehydrated and the nickel cobalt hydroxide precursor material Ni 0.82 Co 0.12 Mn 0.06 (OH)2 was weighed in a molar ratio of 1.07:1 and put into a mixing equipment for mixing. The speed of the mixing equipment was 2500 rpm and the mixing time was 4 minutes. The mixed material was uniformly obtained. The bulk density was tested and the result was 0.60 g·cm -3 (AD1), the tap density test result is 1.38 g cm -3 .
[0131] (2) Weigh the mixed material obtained in step (1) and put it into 90% of the volume of the sagger (the loading amount is 90%, that is, the mass of the mixed material is 1144.86g, that is, m1=1144.86g), then place the sagger in a sintering furnace for low-temperature dehydration, and continuously introduce dry compressed air, the gas flow rate is 3.0L / min, the heating rate is 3℃ / min, the temperature is raised to 160℃, the insulation time is 180min, and the low-temperature dehydrated material (i.e., dehydrated material) is obtained after cooling. The halogen moisture analysis is 0.29MC% (mass fraction), the low-temperature dehydrated material is subjected to secondary mixing, and the loose density is tested, and the result is 0.78g·cm -3 (AD2) was tested for tap density, and the result was 1.46 g cm -3 , the mass m2 after dehydration is weighed to be 1021.22g.
[0132] That is, (AD2-AD1) / AD1=30%. (m1-m2) / m1=10.8%. The dehydrated material prepared in this embodiment is composed of the nickel cobalt hydroxide precursor material Ni 082 Co 012 Mn 006 It is composed of (OH)2 and LiOH (anhydrous lithium hydroxide).
[0133] Furthermore, the preparation method of the positive electrode material provided in this embodiment comprises the following steps: weighing the dehydrated material obtained in the above step (2) and putting it into 90% of the volume of the sagger (that is, the mass of the dehydrated material is 1501.99g), pre-sintering in a sintering furnace, the atmosphere is oxygen, the gas flow rate is 3.0L / min, the heating rate is 4°C / min, the temperature is raised to 625°C, the holding time is 6.5h, and the pre-sintered material is obtained after cooling. The mass loss of the material is determined to be 20.02%. The bulk density of the pre-sintered material is tested, and the result is 1.65g·cm -3 , and the tap density test was performed, the result was 2.35 g·cm -3 The pre-sintered material was sintered in an oxygen atmosphere with a gas flow rate of 3.0 L / min and a heating rate of 4°C / min. The temperature was raised to 765°C for 12 hours and the positive electrode material was obtained after cooling.
[0134] Example 2
[0135] The method for preparing the dehydrated material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (2), the temperature of low-temperature dehydration is 180°C.
[0136] Referring to the preparation method of the positive electrode material in Example 1, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0137] Example 3
[0138] The method for preparing the dehydrated material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (2), the temperature of low-temperature dehydration is 200°C.
[0139] Referring to the preparation method of the positive electrode material in Example 1, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0140] Example 4
[0141] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Embodiment 1, except that in step (2), the temperature of low-temperature dehydration is 220°C.
[0142] Referring to the preparation method of the positive electrode material in Example 1, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0143] Example 5
[0144] The method for preparing the dehydrated material provided in this embodiment comprises the following steps:
[0145] According to the molar ratio of the lithium source to be dehydrated to the nickel cobalt hydroxide precursor material of 1.05:1, 4802.65g of nickel cobalt hydroxide precursor material Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and 2200.31g of the lithium source LiOH·H2O to be dehydrated were placed in a high-speed mixing device for mixing. The speed of the high-speed mixing device was 1500rpm and the mixing time was 10min. A uniformly mixed material was obtained. The bulk density test result was 0.62g·cm -3 (AD1), the tap density test result is 1.49 g cm -3 .
[0146] Then the speed of the high-speed mixer was reduced to 300rpm, the temperature was set to 120℃, the air pressure was 0.03MPa, and low-temperature dehydration was performed for 120min. After cooling, the low-temperature dehydrated material (i.e., dehydrated material) was obtained. The bulk density was tested and the result was 0.79g·cm -3 , and the tap density test was performed, and the result was 1.50 g·cm -3 The halogen moisture content was 0.37 MC%, and the specific surface area test was 5.44 m 2 / g, the mass loss of the material is (m1-m2) / m1=9.82%. In this embodiment, (AD2-AD1) / AD1=27.42%. The dehydrated material prepared in this embodiment is composed of nickel cobalt hydroxide precursor material Ni 0.9 Co 0.05 Mn 0.05 It is composed of (OH)2 and LiOH (anhydrous lithium hydroxide).
[0147] Furthermore, the method for preparing the positive electrode material provided in this embodiment comprises the following steps:
[0148] The dehydrated material prepared above was weighed and put into 90% of the volume of the sagger (i.e., the mass of the dehydrated material was 1466.83 g), and pre-sintered in a sintering furnace. The atmosphere was air, the air flow rate was 2.0 L / min, the heating rate was 3 ° C / min, the temperature was raised to 625 ° C, the holding time was 6 h, and after cooling, 1225.39 g of the pre-sintered material was obtained, that is, the mass loss of the material was 16.46%. The bulk density of the pre-sintered material was tested, and the result was 1.56 g cm -3 , and the tap density test was performed, the result was 2.51 g·cm -3 .
[0149] The pre-sintered material was sintered in an oxygen atmosphere with a gas flow rate of 4.0 L / min and a heating rate of 3°C / min. The temperature was raised to 720°C and the heat preservation time was 14 h. After cooling, the positive electrode material was obtained.
[0150] Example 6
[0151] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Embodiment 5, except that the rotation speed during the mixing process (before dehydration) is replaced with 2000 rpm.
[0152] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0153] Example 7
[0154] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Embodiment 5, except that the rotation speed during the mixing process (before dehydration) is replaced with 1000 rpm.
[0155] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0156] Example 8
[0157] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Embodiment 5, except that the mixing time during the mixing process (before dehydration) is replaced with 2 minutes.
[0158] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0159] Example 9
[0160] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Embodiment 5, except that the mixing time during the mixing process (before dehydration) is replaced with 4 minutes.
[0161] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0162] Example 10
[0163] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Embodiment 5, except that the mixing time during the mixing process (before dehydration) is replaced with 6 minutes.
[0164] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0165] Embodiment 11
[0166] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Embodiment 9, except that the temperature of the low-temperature dehydration is replaced with 140°C.
[0167] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0168] Example 12
[0169] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Embodiment 9, except that the temperature of the low-temperature dehydration is replaced with 160°C.
[0170] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0171] Embodiment 13
[0172] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Embodiment 9, except that the temperature of the low-temperature dehydration is replaced with 180°C.
[0173] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0174] Embodiment 14
[0175] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Example 13, except that the dehydration time is replaced with 70 minutes.
[0176] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0177] Embodiment 15
[0178] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Example 13, except that the dehydration time is replaced with 90 minutes.
[0179] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0180] Example 16
[0181] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in embodiment 1, except that in step (1), the nickel cobalt hydroxide precursor material is replaced by Ni 0.8 Co 0.1 Mn 0.06 Ta 0.02 Sr 0.01 Nb 0.01 (OH)2.
[0182] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0183] Embodiment 17
[0184] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Example 1, except that: in step (2), the loading amount is replaced with 80%, the introduced gas is replaced with nitrogen, and the introduction flow rate of nitrogen is 1.0 L / min.
[0185] Referring to the preparation method of the positive electrode material in Example 1, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0186] Embodiment 18
[0187] The preparation method of the dehydrated material provided in this embodiment is basically the same as that in Embodiment 5, except that during the low-temperature dehydration process, the air pressure is controlled to be 0.02 Mpa.
[0188] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material prepared in this example is pre-sintered and sintered in sequence to obtain the positive electrode material.
[0189] Comparative Example 1
[0190] The preparation method of the positive electrode material provided in this comparative example comprises the following steps:
[0191] (1) The same as step (1) of Example 1, namely, a uniformly mixed material is obtained.
[0192] (2) Weigh the mixed material obtained in step (1) and put it into 90% of the volume of the sagger (the mass of the mixed material is 1133.27g), and pre-sinter it in a sintering furnace. The atmosphere is oxygen, the gas flow rate is 3.0L / min, the heating rate is 4℃ / min, the temperature is raised to 625℃, the heat preservation time is 6.5h, and the pre-sintered material is obtained after cooling. The mass loss of the material is measured to be 27.95%. The pre-sintered material is sintered in an oxygen atmosphere, the gas flow rate is 3.0L / min, the heating rate is 4℃ / min, the temperature is raised to 725℃, the heat preservation time is 12h, and the positive electrode material is obtained after cooling.
[0193] That is, in Comparative Example 1, no low-temperature dehydration step was performed before pre-sintering.
[0194] Comparative Example 2
[0195] The preparation method of the positive electrode material provided in this comparative example comprises the following steps: according to the molar ratio of the lithium source to be dehydrated to the nickel cobalt hydroxide precursor material of 1.05:1, 4802.65 g of the nickel cobalt hydroxide precursor material Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and 2200.31g of the lithium source LiOH·H2O to be dehydrated are mixed in a vacuum mixing device, wherein the speed of the device is 1500rpm and the mixing time is 10min to obtain a uniformly mixed material. The uniformly mixed material is weighed and put into 90% of the volume of the sagger (mass is 1130.31g), and pre-sintered in a sintering furnace. The atmosphere is air, the gas flow rate is 2.0L / min, the heating rate is 3℃ / min, the temperature is raised to 625℃, the insulation time is 6h, and the pre-sintered material is obtained after cooling. The material mass loss is 28.03%. After that, the pre-sintered material is sintered in an oxygen atmosphere, the gas flow rate is 4.0L / min, the heating rate is 3℃ / min, the temperature is raised to 750℃, the insulation time is 15h, and the positive electrode material is obtained after cooling.
[0196] That is, in Comparative Example 2, no low-temperature dehydration step was performed before pre-sintering.
[0197] Comparative Example 3
[0198] The preparation method of the dehydrated material provided in this comparative example comprises the following steps:
[0199] (1) The lithium source LiOH·H2O to be dehydrated is placed into 90% of the volume of the sagger, and then the sagger is placed in a sintering furnace for dehydration, and dry compressed air is continuously introduced, the gas flow rate is 3.0 L / min, the heating rate is 3°C / min, the temperature is increased to 160°C, the insulation time is 180 min, and the dehydrated lithium hydroxide is obtained after cooling.
[0200] (2) the dehydrated lithium hydroxide and nickel cobalt hydroxide precursor material Ni obtained in step (1) are mixed with 0.82 Co 0.12 Mn 0.06 (OH)2 is weighed at a molar ratio of 1.07:1 and put into a mixing equipment for mixing. The rotation speed of the mixing equipment is 2500 rpm and the mixing time is 4 minutes to obtain a uniformly mixed material, i.e., a dehydrated material.
[0201] That is, in this comparative example, the lithium source is first dehydrated and then mixed with the precursor.
[0202] Referring to the preparation method of the positive electrode material in Example 1, the dehydrated material obtained in this comparative example was pre-sintered and sintered in sequence to obtain the positive electrode material.
[0203] Comparative Example 4
[0204] The preparation method of the dehydrated material provided in this comparative example is basically the same as that in Example 5, except that the low-temperature dehydration is carried out under normal pressure.
[0205] Referring to the preparation method of the positive electrode material in Example 5, the dehydrated material obtained in this comparative example was pre-sintered and sintered in sequence to obtain the positive electrode material.
[0206] The bulk density AD1 (in g / cm2) of the uniformly mixed materials obtained after mixing in each embodiment and each comparative example was measured respectively. 3 ) and tap density TD1 (in g / cm 3 ), the results are shown in Table 1. The bulk density AD2 (in g / cm 3 ), tap density TD2 (unit: g / cm 3) and the mass fraction of water ω (wt.%) therein were measured, and the mass loss rate after dehydration (m1-m2) / m1 (wherein m1 is the sum of the masses of the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated before dehydration, and m2 is the mass of the dehydrated material after dehydration) and the value of the bulk density increase rate after dehydration (AD2-AD1) / AD1 were calculated. The results are shown in Table 1. The bulk density AD3 (unit: g / cm 3 ) and tap density TD3 (in g / cm 3 ), and the results are shown in Table 1.
[0207] In each embodiment and each comparative example, the loading amount V1 of the sagger of the mixed material obtained after mixing, the loading amount V2 of the sagger of the dehydrated material obtained after dehydration, and the loading amount increase rate ((V2-V1) / V1) are shown in Table 2. Li2CO3, LiOH and Li in the dehydrated material obtained in each embodiment and each comparative example + The contents are shown in Table 2.
[0208] Table 1 Material properties
[0209]
[0210] Table 2 Loading capacity and lifting rate
[0211]
[0212]
[0213] Tables 1 and 2 illustrate that the dehydrated materials provided by the present invention have low moisture content, high bulk density, large tap density, and high loading capacity. Specifically, after mixing, dehydration occurs, and as the temperature increases, the bulk density of the dehydrated material increases. During dehydration during the mixing process, the dehydration time can be shortened from 3 hours to 2 hours, and the bulk density and loading capacity are further improved. The bulk density is increased by more than 16%, and Example 13 even increases by 39.06%. The increase in bulk density increases the material loading capacity per unit volume, and the sagger loading capacity can also be increased by more than 27%, thereby increasing the capacity of the pre-sintering process. For a single production line, the annual output is increased by more than 27%, which is of great significance to actual production.
[0214] However, in Comparative Example 4, low-temperature dehydration is performed under normal pressure, resulting in that water vapor cannot be discharged in time and the dehydration effect of the lithium source is poor.
[0215] In addition, compared with the comparative examples, the content of LiOH and Li +The content is higher, which indicates that the dehydration efficiency of each embodiment is higher. The reason why Li2CO3 exists in a small amount is that LiOH easily absorbs water and easily reacts with CO2 in the air to generate Li2CO3.
[0216] Experimental Example 1
[0217] The dehydrated materials and positive electrode materials prepared in each embodiment and in each ratio were observed by field emission scanning electron microscope, and the length L and width W (definition: the particles were converted into rectangles with equal area and closest shape, with the long side of the rectangle being the length L and the short side being the width W) of 80 visible primary particles (primary particles of positive electrode materials) were measured and counted according to the appropriate magnification of the micrographs, and then the ratio W / L of the two was calculated. The primary particle size of each positive electrode material is shown in Table 3. The morphology characterization results of Examples 1 to 4 are shown in Table 3. Figures 1 to 12 Specifically, the SEM images of the dehydrated materials obtained in Example 1, Example 2, Example 3 and Example 4 are shown in FIG. Figure 1 , Figure 2 , Figure 3 and Figure 4 The cross-sectional SEM (CP-SEM) images of the dehydrated materials obtained in Example 1, Example 2, Example 3 and Example 4 are shown in FIG. Figure 5 , Figure 6 , Figure 7 and Figure 8 The SEM images of the positive electrode materials prepared in Example 1, Example 2, Example 3 and Example 4 are shown in FIG. Fig. 9 , Fig.10 , Fig.11 and Fig.12 As shown. Figure 1-Figure 8 It can be seen that low-temperature dehydration at different temperatures does not change the morphology of the material.
[0218] Table 3 Primary particle size results of each positive electrode material
[0219] Group Length L / nm Width W / nm W / L Example 1 543.57 348.89 0.64 Example 2 599.79 382.37 0.64 Example 3 627.19 411.79 0.66 Example 4 593.51 368.77 0.62 Example 5 441.28 247.26 0.56 Example 6 465.32 243.17 0.52 Example 7 432.47 275.42 0.64 Example 8 387.35 225.93 0.58 Example 9 408.40 251.05 0.61 Example 10 463.36 280.20 0.60 Embodiment 11 431.55 240.77 0.56 Example 12 401.42 234.53 0.58 Embodiment 13 421.34 264.90 0.63 Embodiment 14 517.37 326.18 0.63 Embodiment 15 495.90 314.39 0.63 Example 16 430.27 266.77 0.62 Embodiment 17 469.08 300.21 0.64 Embodiment 18 405.78 255.64 0.63 Comparative Example 1 450.45 277.75 0.62 Comparative Example 2 562.55 326.97 0.58 Comparative Example 3 498.91 299.35 0.60 Comparative Example 4 507.99 299.71 0.59
[0220] The positive electrode materials prepared in each embodiment and each ratio were tested by powder X-ray diffractometer, with the acceleration voltage and current being 40 kV and 100 mA, respectively, the scanning speed being 5 ° / min, and the scanning range being 10 ° to 80 °, and then the area ratio of the peak (003) to the peak (104) in the curve was calculated I(003) / I(104). The unit cell parameters of each positive electrode material and the area ratio of the peak (003) to the peak (104) I(003) / I(104) characterization results are shown in Table 4.
[0221] Table 4 Crystal constants and I(003) / I(104) results of various positive electrode materials
[0222]
[0223]
[0224] Table 3, Table 4 and Figures 9 to 12 It is shown that the embodiments and proportions using different process parameters in mixing and dehydration have no obvious changes in the morphology, primary particle size and crystal structure of the final product (positive electrode material), which indicates that the method of low-temperature dehydration mixing before formal sintering or pre-sintering will not cause changes in the grain size and crystal structure of the final product (positive electrode material) while increasing the amount of sagger. Therefore, the present invention can greatly improve production capacity while ensuring product quality.
[0225] Experimental Example 2
[0226] In order to explore the effect of different temperatures and times on the degree of dehydration of the material, the precursor and the lithium source were mixed (i.e., the uniformly mixed material obtained by step (1) of Example 1), and the product was analyzed by a thermogravimetric analyzer to specifically explore the effect of different temperatures on the degree of dehydration of the material. The temperature range during the test was 30°C to 160°C, 180°C, 200°C, and 220°C, with a heating rate of 3°C / min. After heating to the target temperature, the temperature was kept for 4 hours, and the gas condition during the entire heating and holding process was air. The thermogravimetric analysis curves of the target temperatures of 160°C, 180°C, 200°C, and 220°C were compared. Fig.13 shown.
[0227] It can be found that when the dehydration temperature is 160-200°C, the mass loss is the same after 4 hours, and when the temperature reaches 220°C, a new weight loss platform can be found after 4 hours. At this time, dehydration of the precursor occurs. Once the precursor is dehydrated and becomes oxide in the low-temperature dehydration stage, and the temperature cannot reach pre-sintering or formal sintering, it will affect the entry of the lithium source and make the performance of the positive electrode material worse. Therefore, in order to achieve the effect of dehydrating the mixture while saving energy consumption, the preferred mixture dehydration temperature is below 200°C.
[0228] Experimental Example 3
[0229] The positive electrode materials prepared in each embodiment and each comparative example were mixed with PVDF binder and conductive carbon black in a mass ratio of 9:0.5:0.5, and N-methylpyrrolidone solvent was added thereto and stirred thoroughly to form a uniform slurry, and then evenly coated on aluminum foil, and then dried, compacted and punched to form a positive electrode sheet of a button battery, and assembled with a lithium sheet as a negative electrode to form a button battery, and tested at room temperature, the voltage range was 2.8 to 4.25V, and the results are shown in Table 5. Among them, the cycle performance comparison of Examples 1 to 4 and Comparative Example 1 is shown in Fig.14The charge and discharge curves of Example 1 at different current densities are as follows Fig.15 The cycle performance comparison of Example 5 and Comparative Example 2 is shown in Fig.16 The charge and discharge curves of Example 5 at different current densities are as follows Fig.17 shown.
[0230] Among them, the electrochemical performance test method is as follows: the assembled button battery is left to stand for 10 hours, and then the electrochemical test is started. The first two cycles are activation processes, the first charge rate is 0.1C, the discharge rate is 0.1C, the second charge rate is 0.3C, the discharge rate is 0.3C, the third charge rate is 0.5C, and the discharge rate is 0.5C. Then the long cycle test is started, the charge and discharge rates are 0.5C / 1C respectively, and the charge and discharge cut-off voltage is 2.8~4.25V.
[0231] Table 5 Comparison of electrochemical performance of each battery
[0232]
[0233]
[0234] It can be seen from Table 5 that the batteries prepared in each embodiment have higher capacity, first coulombic efficiency and capacity retention rate.
[0235] However, in Comparative Examples 1 and 2, low-temperature dehydration was not performed before pre-sintering, resulting in a significant decrease in cycle performance.
[0236] In Comparative Example 3, the lithium source is first dehydrated and then mixed with the precursor, resulting in poor drainage of a large amount of water in the lithium source, and then insufficient dehydration, which generates water vapor when the mixture is sintered with the precursor, affecting the performance of the material.
[0237] Comparative Example 4 uses low-temperature dehydration under normal pressure, which results in that the water cannot be discharged in time, the dehydration efficiency is low, and the water content of the material after dehydration is high, which leads to a decrease in performance.
[0238] In summary, the present invention sets a low-temperature dehydration process before pre-sintering to remove water in the lithium source in advance, so that the lithium source particles become smaller, which can increase the loose density of the material after mixing, and then significantly increase the loading capacity of the unit volume of the sagger during subsequent pre-sintering or formal sintering, thereby improving the sintering yield, significantly improving the production capacity of a single production line, and achieving a production capacity plan matching the formal sintering without increasing the sintering equipment.
[0239] In addition, the present invention dehydrates the lithium source during the mixing process, such as Fig.18As shown, the mixing and dehydration processes are carried out simultaneously in the high-speed flow mixer, which can remove part of the water in the raw materials in advance. Thanks to the existence of the slight negative pressure in the mixer, the generated water vapor will be quickly discharged, which can significantly shorten the dehydration time and further improve the production efficiency. After the lithium source in the raw material is dehydrated, a large amount of water vapor generated during sintering is reduced, making it easier for the lithium source to form a layered oxide with the precursor, and the bulk density of the material is increased after low-temperature dehydration. Experimental results show that compared with the traditional process, the dehydration mass of the present invention can reach 13.5% after low-temperature dehydration treatment, the unit sagger loading capacity can be increased by more than 27% after low-temperature dehydration, and the actual bulk density is increased by more than 16%, and it will not cause performance degradation to the final positive electrode material product. By adopting the preferred process parameters, the initial discharge specific capacity can be ≥192.3mAh / g, and after 50 cycles, the reversible specific capacity of ≥181.95mAh / g can still be obtained, and the cycle capacity retention rate is ≥97.2%. The low-temperature dehydration mixing technology significantly improves the capacity of the pre-sintering process, and indirectly for a single production line, the annual output of the pre-sintering capacity is increased by more than 27%.
[0240] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A dehydrated material, characterized in that: It is mainly composed of nickel cobalt hydroxide precursor material and lithium source; The bulk density of the dehydrated material is 0.75-1.5 g / cm 3 ; The mass fraction of water in the dehydrated material is less than 0.4 wt%.
2. The dehydrated material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The chemical formula of the nickel-cobalt hydroxide precursor material is Ni x Co y M 1-x-y (OH)2, where 0 < x < 1, 0 < y < 1, 0 ≤ 1 - x - y ≤ 0.2, and M includes at least one of Co, Al, Ta, Mn, Zr, Mg, Ca, Ge, Y, W, B, Ce, Sr, Nb, and Ti elements; preferably, 0.8 ≤ x < 1; (2) The lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate; (3) The molar ratio of the nickel cobalt hydroxide precursor material to the lithium element in the lithium source is 1:0.7-1.2; (4) The molar ratio of the nickel cobalt hydroxide precursor material to the lithium element in the lithium source is 1:0.95-1.1; (5) The tap density of the dehydrated material is 1.38 to 1.7 g / cm 3 .
3. The method for preparing the dehydrated material according to claim 1 or 2, characterized in that: The method comprises the following steps: mixing a nickel-cobalt hydroxide precursor material and a lithium source to be dehydrated, and then dehydrating the mixture under the condition of continuous introduction of gas or negative pressure to obtain the dehydrated material.
4. The method for preparing the dehydrated material according to claim 3, characterized in that: The preparation method of the dehydrated material specifically comprises: mixing the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated, loading the mixture into a sagger, placing the mixture in a sintering device, continuously introducing gas, and performing the dehydration at 100-300° C.; Preferably, the loading amount of the sagger is 70% to 100% of the volume of the sagger, more preferably 85% to 95%; Preferably, the gas comprises air and / or nitrogen; Preferably, the gas flow rate is 0.1 to 5 L / min, more preferably 0.5 to 3 L / min.
5. The method for preparing the dehydrated material according to claim 3, characterized in that: The preparation method of the dehydrated material specifically comprises: mixing the nickel cobalt hydroxide precursor material and the lithium source to be dehydrated in a mixing device, after the mixing is completed, reducing the speed of the mixing device, and increasing the temperature of the mixing device, and performing the dehydration at 100-300° C. under negative pressure conditions; Preferably, the rotation speed of the mixing device is reduced to 100-1000 rpm, more preferably 100-600 rpm; Preferably, the dehydration time is 60 to 180 minutes; Preferably, the dehydration gas pressure is 0.02-0.07 MPa, more preferably 0.02-0.04 MPa.
6. The method for preparing the dehydrated material according to claim 3, characterized in that: At least one of the following conditions is met: (1) The mixing speed is 300 to 3500 rpm; (2) The mixing speed is 1000 to 3000 rpm; (3) The mixing time is 1 to 20 minutes; (4) The mixing time is 3 to 10 minutes; (5) The dehydration temperature is 140-240° C.; (6) The dehydration time is 30 to 480 minutes; (7) The dehydration time is 60 to 240 minutes; (8) The sum of the masses of the nickel-cobalt hydroxide precursor material and the lithium source to be dehydrated before the dehydration is m1, and the mass of the dehydrated material obtained after the dehydration is m2, (m1-m2) / m1=9% to 40%; (9) The bulk density of the mixed material obtained after the mixing is AD1, and the bulk density of the dehydrated material obtained after the dehydration is AD2, (AD2-AD1) / AD1=16% to 40%; (10) The lithium source to be dehydrated includes at least one of lithium hydroxide monohydrate, anhydrous lithium hydroxide, lithium carbonate, lithium acetate and lithium nitrate.
7. A positive electrode material, characterized in that: Mainly prepared from the dehydrated material as claimed in claim 1 or 2; Preferably, the bulk density of the positive electrode material is 1.5 to 1.9 g / cm 3 ; Preferably, the tap density of the positive electrode material is 2.3 to 2.6 g / cm 3 .
8. The method for preparing the positive electrode material according to claim 7, characterized in that: The method comprises the following steps: pre-sintering and sintering the dehydrated material in sequence.
9. A positive electrode sheet, characterized in that: Comprising the positive electrode material as claimed in claim 7.
10. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.